2021
DOI: 10.7759/cureus.20486
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Complementary and Alternative Medicine Among Pediatricians in Saudi Arabia

Abstract: BackgroundComplementary and Alternative Medicine (CAM) refers to a variety of healthcare practices outside the domain of conventional medicine, which may be integrated with conventional medicine by many physicians. ObjectivesThis study aims to assess the attitudes and beliefs of pediatricians toward the use of CAM on children and to evaluate their knowledge and experience regarding CAM therapies and their desire for additional CAM training courses. MethodsThis is a cross-sectional study that was conducted in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Art therapy, play therapy, and clowns are other supportive care modalities offered in children's wards (including oncology) in Norway [ 49 – 52 ]. Even though CAM is used by pediatric oncology patients [ 53 ], according to the literature, there is a lack of knowledge about CAM among pediatric oncologists [ 54 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Art therapy, play therapy, and clowns are other supportive care modalities offered in children's wards (including oncology) in Norway [ 49 – 52 ]. Even though CAM is used by pediatric oncology patients [ 53 ], according to the literature, there is a lack of knowledge about CAM among pediatric oncologists [ 54 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that most of the participants from KSA are aware enough not to use CAM interventions without an appropriate consultation. A few studies reported that almost half of CAM users consulted with or disclosed to physicians about the use of CAM [19][20][21]. Unwillingness to stop using CAM was one of the most common reasons for non-disclosure [21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, customary treatments such as cautery and the utilization of camel milk are widely embraced. Traditional healers constitute the primary sources of traditional medicine [48,49].…”
Section: The State Of Conventional and Alternative Medicine In Saudi ...mentioning
confidence: 99%
“…Notably, breaches in physical security are a significant contributor to security breaches overall, ranking second [49]. Assigning specific security responsibilities exemplifies a physical safeguarding approach [48].…”
Section: Security and Privacy Features Of Current Ehr Systemsmentioning
confidence: 99%